Identifying the Importance of Disaster Resilience Dimensions across Different Countries Using the Delphi Method - Rodriquez, Carlotta (2022)
Supplementary Materials: The following are available online at https://www.mdpi.com/article/10.3390/su14159162/s1, Figure S1: Results of the internal cluster validity indices, S8: Survey used in the Delphi process, Table S1: Countries selected in the research, Table S2: Imputation of missing values: identification of the nearest neighbors, geographical meaningfulness, and availability of data, Table S3: Clusters of countries considering 3 clusters, Table S4: Clusters of countries considering 4 clusters, Table S5. Clusters of countries considering 5 clusters, Table S6: Clusters of countries considering 6 clusters, Table S7: First structure of the proposed DRI, Table S8: Average scores (sc) and normalized weights (w) of the Social sub-dimensions by cluster, Table S9: Average scores (sc) and normalized weights (w) of the Economic sub-dimensions by cluster, Table S10: Average scores (sc) and normalized weights (w) of the Environmental sub-dimensions by cluster, Table S11: Average scores (sc) and normalized weights (w) of the Habitat sub-dimensions by cluster, Table S12: Average scores (sc) and normalized weights (w) of the Infrastructure sub-dimensions by cluster, Table S13: Average scores (sc) and normalized weights (w) of the Institutional sub-dimensions by cluster.